2019
DOI: 10.3389/fmicb.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

13C-Metabolic Flux Analysis Reveals the Metabolic Flux Redistribution for Enhanced Production of Poly-γ-Glutamic Acid in dlt Over-Expressed Bacillus licheniformis

Abstract: Poly-γ-glutamic acid (γ-PGA) is an anionic polymer with various applications. Teichoic acid (TA) is a special component of cell wall in gram-positive bacteria, and its D-alanylation modification can change the net negative charge of cell surface, autolysin activity and cationic binding efficiency, and might further affect metabolic production. In this research, four genes (dltA, dltB, dltC, and dltD) of dlt operon were, respectively, deleted and overexpressed in the γ-PGA producing strain Bacillus licheniformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…WTA has essential physiological functions in cell division, drug resistance, and biofilm formation ( 56 58 ). Moreover, it has been reported that the yield of different secreted products could be improved by altering WTA degradation in Escherichia and changing the d -alanylation modification of WTA in Bacillus ( 59 61 ). However, in actinomycetes the mechanisms of WTA synthesis and regulation are poorly understood ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…WTA has essential physiological functions in cell division, drug resistance, and biofilm formation ( 56 58 ). Moreover, it has been reported that the yield of different secreted products could be improved by altering WTA degradation in Escherichia and changing the d -alanylation modification of WTA in Bacillus ( 59 61 ). However, in actinomycetes the mechanisms of WTA synthesis and regulation are poorly understood ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…While, the high viscosity of γ-PGA decreased the concentrations of dissolved oxygen and limited the absorption or utilization of nutrients during the fermentation, which property hindered the cell growth and the synthesis of γ-PGA (Hsueh et al 2017). Previous study in our lab found that the decrease of negative charge on cell wall surface could significantly improve cell growth and γ-PGA production in B. licheniformis (He et al 2019). So, cell wall properties are closely related to cell growth and γ-PGA synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…Cell growth curve was determined by measuring the optical density at 600 nm (OD600) in LB medium. γ-PGA titer and biomass were detected by the method described in the previous research (He et al 2019). Concentrations of acetoin, 2,3-butanediol and acetic acid were quantified using Thermo Scientific GC-MS (Thermo, USA) equipped with TG-WAXMS column (30 m × 0.32 mm ID, 0.25 μm film) by an optimized method from previous research (Qi et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…While these foundational metabolic features have been clearly established, the metabolic rewiring of P. putida strains in response to complex engineering of central pathways is unknown. Many studies in microbes have examined flux changes in response to simple genetic edits ( i.e., deletion or overexpression ( He et al, 2019 ; Long and Antoniewicz, 2019b ; Long et al, 2016 ; Xu et al, 2021 ), however the impact of transcriptional downregulation due to multiplexed CRISPRi on flux topology has not been examined in-depth in any microbe. Due to the complexity and technical challenges needed to accurately quantify metabolic flux, previous researchers have used gene expression analysis (RNAseq) as a proxy in these engineered strains ( Reis et al, 2019 ; Silvis et al, 2021 ; Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%